Daunorubicin Down‐Regulates the Expression of Stem Cell Markers and Factors Involved in Stem Cell Migration and Homing in Rat Heart in Subchronic but not Acute Cardiomyopathy. Issue 5 (20th May 2016) - Srankova, Jasna; Doka, Gabriel; Pivackova, Lenka; Mesarosova, Lucia; Kyselovic, Jan; Klimas, Jan; Krenek, Peter
Abstract: We tested the hypothesis that daunorubicin (DAU) cardiotoxicity alters expression of cytokines involved in stem cell migration and homing. Male Wistar rats were treated with daunorubicin to induce acute DAU cardiomyopathy (6 × 3 mg/kg, i.p., every 48 hr, DAU‐A) or subchronic DAU cardiomyopathy (15 mg/kg, i.v., DAU‐C). The left ventricle was catheterized. The animals were killed 48 hr (DAU‐A) and 8 weeks (DAU‐C) after the last dose of DAU. Expression of foetal genes (Nppa, Nppb), isomyosins (Myh6, Myh7), sources of oxidative stress (Abcb8, gp91phox), cytokines (Sdf‐1, Cxcr4, Scf, Vegf, Hgf, Igf‐1), markers of cardiac progenitor (c‐kit, Atnx‐1), endothelial progenitor (CD34, CD133) and mesenchymal (CD44, CD105) stem cells were determined by qRT‐PCR in left ventricular tissue. Reduced body‐weight, decreased left ventricular weight and function, and elevated Nppa, Nppb, Myh7 were observed in both models. Myh6 decreased only in DAU‐C, which had a 35% mortality. Up‐regulated gp91phox and down‐regulated Abcb8 in DAU were present only in DAU‐C where we observed markedly decreased expressions of Scf and Vegf as well as expressions of stem cell markers. Down‐regulation of cytokines and stem cell markers may reflect impaired chemotaxis, migration and homing of stem cells and tissue repair in the heart in subchronic but not acute model of DAU cardiomyopathy.